Termination of Employment Based on Employee’s HIV Status: The Response of the National Industrial Court of Nigeria - Ajayi, Mary-Ann Onoshioke; Tarh-Akong Eyongndi, David (The Age of Human Rights Journal, 2023)
This article adopts desk-based methodology in interrogating the issue of HIV related employment termination in Nigeria, focusing on the National Industrial Court of Nigeria (NICN) decision in Akinola v. Ocean Marine Solutions Ltd. It examined international and domestic legal frameworks on the subject, the human rights affected by such termination, the impact of the decision taken on the protection of the human cum employment rights of employees living with HIV/AIDS and the response of the NICN to the quagmire. It observed that the quantum of damages awarded by the NICN cannot achieve deterrence. It recommends how to eradicate HIV related employment termination in Nigeria.